Penerapan Framework COBIT untuk Meningkatkan Penataan dan Pengelolaan Perjalanan Dinas Pegawai di Dinas Komunikasi, Informatika dan Statistik Provinsi Bali - Sanjaya, Ngurah Bagus; Indriyani, I. (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2024)
The Department of Communication, Informatics, and Statistics of Bali Province is responsible for assisting the Governor in managing governmental affairs in communication, informatics, statistics, and cryptography, as regulated by Bali Province Governor Regulation Number 71 of 2022. This study aims to monitor official trips of employees at Diskominfos Bali Province using the COBIT framework. The research employs a qualitative approach, with employees of Diskominfos as the research subjects. Data collection methods include interviews, questionnaires, documentation, and observation. Data analysis is conducted using content analysis techniques to evaluate the effectiveness and efficiency of official travel governance. The study concludes that good governance practices based on COBIT strengthen the organization ability to face challenges and support the achievement if its vision and mission.